Use of Placental Growth Factor for Trisomy 21 Screening in Pregnancy: A Systematic Review - Ahmad Badeghiesh; Alexander Volodarsky-Perel; Ariane Lasry; Robert Hemmings; Yaron Gil; Jacques Balayla (Thieme Medical Publishers, Inc., 2020)
Background Prenatal serum screening is an important modality to screen for aneuploidy in pregnancy. The addition of placental growth factor (PLGF) to screen for trisomy 21 remains controversial. Objective To determine whether the addition of PLGF to combined serum aneuploidy screening improves detection rates (DRs) for trisomy 21. Study Design We performed a systematic review of the literature until October 2019 to determine the benefits of adding PLGF to prenatal screening. We performed a goodness-of-fit test and retrieved the coefficient of determinations (R 2) as a function of false positive rates (FPRs), providing mean-weighted improvements in the DRs after accounting for PLGF levels. Results We identified 51 studies, of which 8 met inclusion criteria (834 aneuploidy cases and 105,904 euploid controls). DRs were proportional to FPR across all studies, ranging from 59.0 to 95.3% without PLGF and 61.0 to 96.3% with PLGF (FPR 1-5%). Goodness-of-fit regression analysis revealed a logarithmic distribution of DRs as a function of the FPR, with R 2 = 0.109 (no PLGF) and R 2 = 0.06 (PLGF). Two-sample Kolmogorov-Smirnov's test reveals a p-value of 0.44. Overall, addition of PLGF improves DRs of 3.3% for 1% FPR, 1.7% for 3% FPR, and 1.4% for 5% FPR, respectively. Conclusion Addition of PLGF to prenatal screening using serum analytes mildly improves trisomy 21 DRs as a function of FPRs.